1989
DOI: 10.1128/jvi.63.3.1338-1344.1989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of attenuation of the Sabin type 3 oral poliovirus vaccine

Abstract: The poliovirus type 3 Sabin oral poliovirus vaccine strain P3/Leon/12a,b differs in nucleotide sequence from its neurovirulent progenitor P3/Leon/37 by just 10 point mutations. The contribution of each mutation to the attenuation phenotype of the vaccine strain was determined by the construction of a series of recombinant viruses from infectious cDNA clones. The neurovirulence testing of recombinant viruses indicated that the attenuation phenotype is determined by just two point mutations: a C to U in the nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(96 citation statements)
references
References 26 publications
2
94
0
Order By: Relevance
“…This heterogenicity of the PRRSV 5 -end sequence should be further investigated for its relevance. Interestingly, both ends of viral sequences have been shown to not only play an important role in the replication of coronaviruses, another member of the order Nidovirales (Williams et al, 1999), but they are also related to poliovirus attenuation (Westrop et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This heterogenicity of the PRRSV 5 -end sequence should be further investigated for its relevance. Interestingly, both ends of viral sequences have been shown to not only play an important role in the replication of coronaviruses, another member of the order Nidovirales (Williams et al, 1999), but they are also related to poliovirus attenuation (Westrop et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In the guts of vaccinees, such reversions occur very often and quite rapidly at positions 480, 481, and 472 in the RNAs of OPV serotypes 1, 2, and 3, respectively (307-311; reviewed in references 312 to 314), leading to restoration of their somewhat impaired secondary (for serotypes 1 and 3) or tertiary (for serotype 2) structures (104, 311, 315) ( Fig. 4) and, consequently, translational activity (316)(317)(318)(319) and neurovirulence (308,315,320,321).…”
Section: Rehabilitation After Adverse Changes In the Untranslated Regmentioning
confidence: 99%
“…The Sabin OPV strains contain attenuation mutations not only in their IRES elements but also in the encoded proteins (321,(344)(345)(346)(347). Some of them are known to readily revert in vaccinees or during subsequent transmission, resulting in the restoration of viral fitness (reviewed in references 312 and 313).…”
Section: Rehabilitation After Adverse Changes In Viral Proteinsmentioning
confidence: 99%
“…However, one or more of these silent mutations could change the secondary or tertiary structure of PRRSV RNA and thus alter the stability of the genome. In other viruses, such as picornaviruses, viral RNA folding may play a critical role in host protein association (Meerovitch et al, 1989) and in neurovirulence (Pilipenko et al, 1989a,b;Westrop et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The 5% and 3% ends of viral sequences have been correlated with attenuation in other viruses, such as poliovirus (Westrop et al, 1989), and shown to be important in viral replication and transcription for coronaviruses, another member of the Nidovirus order (Williams et al, 1999). Only two mutations occurred in the 5%-end of PRRSV during attenuation of strain VR-2332 to RespPRRS, and their relative roles in attenuation must be further investigated.…”
Section: Discussionmentioning
confidence: 99%